The Idiolect of Wojciech Piotrowicz: A Vocabulary of Autobiographical Prose - Geben, Kinga; Fedorowicz, Irena (Slavistica Vilnensis, 2020)
Wojciech Piotrowicz (born in 1940) is a Vilnius poet, prose writer, translator, journalist, social and cultural activist. He is the author of several poetry collections and volumes of memoirs. Research on which this paper is based consists of two main parts: we present the writer’s biography, which introduces a representative of the Polish intelligentsia in Lithuania, and an analysis of his lexis from his collection of short stories Moja czasoprzestrzeń (My Space-Time) (2015). The aim of the research is to investigate the lexical layers in the idiolect of the writer. Piotrowicz’s idiolect is the domain where the erudite vocabulary of the standard language blends in with the dialectical vocabulary of the Švenčionys district, in which words of rural life are frequent. In the vocabulary of his idiolect, we distinguish the following groups of lexemes: words from family language, archaisms, dialect words, and postwar Russian borrowings, referred to as “Soviet words”. The multi-layer nature of Piotrowicz’s idiolect is a result of a complicated reality on the border between cultures, languages, times, and evidence of changes in social stratification. To summarize the research results, it can be stated that the analysis of 179 words (phrases) from the writer’s individual language shows a world of concepts, thoughts, and values that are characteristic of representatives of the intelligentsia of peasant origin, born in the 1940s. The authors of the paper consider that this study is only a contribution toward determining the peculiarities of the Polish language spoken by the intelligentsia in Lithuania in the 20th century, and that this article does not exhaust all issues of Wojciech Piotrowicz’s idiolect.